2021
DOI: 10.1097/jtn.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognosis of Coma Patients With Acute Brain Injury by Electroencephalogram Bispectral Index Monitoring

Abstract: Background: The high mortality rate of comatose patients with traumatic brain injury is a prominent public health issue that negatively impacts patients and their families. Objective, reliable tools are needed to guide treatment decisions and prioritize resources. Objective: This study aimed to evaluate the prognostic value of the bispectral index (BIS) in comatose patients with severe brain injury. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A large number of studies have shown that the bispectral index (BIS) is currently a very reliable indicator for evaluating the depth of sedation in anesthesia. BIS has received much attention and research in the field of clinical anesthesia [ 8 ]. This article intends to evaluate its application in anesthesia depth monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the bispectral index (BIS) is currently a very reliable indicator for evaluating the depth of sedation in anesthesia. BIS has received much attention and research in the field of clinical anesthesia [ 8 ]. This article intends to evaluate its application in anesthesia depth monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography (EEG) is an established neurological procedure that provides valuable information for estimating and monitoring cerebral function and determines cognitive performances [ 8 ]. In this context, EEG abnormalities have been identified in many investigations as surrogates for the course of diseases as well as for treatment results [ 9 , 10 ]. In conclusion, EEG findings presumably could help to estimate performances in older patients scheduled for CGC.…”
Section: Introductionmentioning
confidence: 99%